THE EFFECT OF MOTIVATION AND COMPENSATION ON EMPLOYEES' WORK SPIRIT AT PT MATAHARI DEPARTMENT STORE Tbk MALL RATU INDAH MAKASSAR - Asdar, Muhammad (Universitas Ichsan Sidenreng Rappang, 2022)
The Influence of Motivation and Compensation on Employee Morale at PT. Matahari Department Store Tbk. Mall Ratu Indah Makassar This study aims to determine whether motivation and compensation affect employee morale at PT. Matahari Department Store Tbk. Ratu Indah Mall Makassar. Collecting data using primary data obtained from questionnaires using the Probability Sampling technique. The population in this study were all permanent employees at PT Matahari Department Store Tbk Mall Ratu Indah Makassar, which amounted to 340 employees and the number of samples determined using the slovin formula was 77 employees. The results of the questionnaire have been tested for validity and reliability. Methods of data analysis using multiple regression techniques. The results show that simultaneously (F test) motivation and compensation together have a positive and significant effect on employee morale, and based on partial hypothesis testing (t-test), the motivation variable has a positive and significant effect on consumer buying interest, while compensation positive and significant effect on consumer buying interest.